EFFECT OF LAND CONFIGURATIONS AND MULCHES ON SOIL MOISTURE CONSERVATION, GROWTH AND YIELD OF MAIZE (Zea mays L.) UNDER RAINFED CONDITIONS - M. UMA DEVI, B. MAHITHA, V. RAMULU, K. AVIL KUMAR and (The Journal of Research, PJTSAU, 2017)
Maize is cultivated in an area of about 8.12 million ha with a production of 19.77 million tones and a productivity of 2.43 t ha-1 in Andhra Pradesh. Agronomic practices such as ridge and furrow, broad bed and furrow, intercropping, strip cropping and cover cropping etc. is recommended to increase infiltration rate of water and reduce the runoff.Mulching is one of the most important moisture conservation practices in rain fed agriculture among various mechanical and agronomic measures that have been reported to reduce the soil erosion and increase in-situ soil moisture storage. Super absorbent polymers (SAP’s) or hydrogels are loosely cross-linked, three dimensional networks of flexible polymer chains that carry dissociated, ionic functional groups and that can absorb fluids of greater than 15 times of their own dry weight (Zohuriaan and Kourosh, 2008).